The Student Room Group
Reply 1
faa
prove by completing the square , that the roots of the equation x^2+2kx+c=0, where k and c are constants, are -k +/- root(k^2-c)

ive got it down to x+kx = root (kx-c) but now im lost... anyone please help?


x^2 + 2kx + c = 0
=> (x + k)^2 - k^2 + c = 0 <-- think you may have gone wrong here
=> (x + k)^2 = k^2 - c (should be (x + k)^2 not (x + kx)^2)
=> (x + k) = +/- sqrt (k^2 - c)
=> x = -k +/- sqrt (k^2 - c)

Jenn xx
Reply 2
lol- its ok, i kept starring until i figured what i had done- but i did it the long way and cancelled out at the end cos i was working with (-4k/2)^2 lol

got there in the end tho!